PENGARUH STRUKTUR MODAL, PROFITABILITAS, KEBIJAKAN DIVIDEN, SALES GROWTH, DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN (Studi Kasus Pada Perusahaan Properti dan Real Estate Yang Terdaftar Pada Bursa Efek Indonesia Tahun 2015-2019) - Jayanti Rosalia; Wikan Budi Utami; Desy Nur Pratiwi (ITB AAS INDONESIA, 2022)
This study aims to examine the effect of capital structure, profitability, dividend policy, sales growth, and firm size on firm value. This type of research includes quantitative research using secondary data obtained from the analysis of financial statements on the website www.idx.co.id. The population in this study are all property and real estate companies listed on the Indonesia Stock Exchange, totaling 77 companies. The method used in selecting the sample is purposive sampling and determining the sample based on the criteria set by the researcher with a result of 45 samples. Based on the results of secondary data processing with multiple linear regression analysis method, F test, t test, it is known that the variables of capital structure, profitability, dividend policy, sales growth, and company size simultaneously have a significant effect on firm value. Partially, the results of this study indicate that capital structure and profitability have a positive and significant effect on firm value. Meanwhile, dividend policy has a positive and insignificant effect on firm value. Sales growth and firm size have a negative and insignificant effect on firm value.